Design and validation of clutch-to-clutch shift actuator using dual-wedge mechanism. (April 2017) - Chen, Li; Liu, Fengyu; Yao, Jian; Ding, Zhao; Lee, Chunhao; Kao, Chi-kuan; Samie, Farzad; Huang, Ying; Yin, Chengliang
Abstract: Clutch-to-clutch shift technology is a key enabler for fast and smooth gearshift for multi gear transmissions. However, conventional hydraulic actuation systems for clutches have drawbacks of oil leakage and low efficiency. Electromechanical devices including wedge mechanism offer potential alternative actuators. The previous studies on the wedge emphasize on self-reinforcement, but neglect self-weakened phenomenon. In this paper, a novel dual-wedge mechanism is proposed to exert self-reinforcement and avoid self-weakened effect by selecting a correct working slope. The design concept and physical structure are thoroughly described. Dynamic models for the actuation system and vehicle powertrain are built for performance validation. The results show that the normal force generated by the wedge under self-reinforced case is 2.74 times that under self-weakened case. Using the same amount of the driving motor current, the upshift can be successfully completed in 0.78 s when the correct slope is used; however, it fails to engage the clutch when the incorrect slope is used due to self-weakened effect. So does the downshift. Moreover, the experimental results of the dual-wedge mechanism using the correct slope are comparable to those from the hydraulic actuator of a conventional automatic transmission.